2019
DOI: 10.1080/23802359.2019.1573121
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the four-lined snake, Elaphe quatuorlineata (Bonnaterre, 1790)

Abstract: Here, we present complete mitochondrial genome of the four-lined snake, Elaphe quatuorlineata (Bonnaterre, 1790) and its comparison with closely related E. sauromates (Pallas, 1814). The complete sequence of the mitogenome is 17,183 bp long and consists of 13 protein-coding genes, two rRNA and 22 tRNA genes, and two control regions. It possesses the same gene order as other mitogenomes of Elaphe spp. and the base composition is as follows: 35.0% (A), 26.7% (C), 25.6% (T), and 12.7% (G), with an A þ T bias (60.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The overall base composition of the mitogenomes in descending order was 34.7/34.6%-A, 26.9/26.9%-C, 25.6/25.7%-T, 12.8/12.8%-G, with an equal A + T bias (60.3%). This composition is almost identical to the published mitogenomes of E. quatuorlineata and E. sauromates 26,34 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The overall base composition of the mitogenomes in descending order was 34.7/34.6%-A, 26.9/26.9%-C, 25.6/25.7%-T, 12.8/12.8%-G, with an equal A + T bias (60.3%). This composition is almost identical to the published mitogenomes of E. quatuorlineata and E. sauromates 26,34 .…”
Section: Resultssupporting
confidence: 83%
“…We had the appropriate permissions to use the snake tissue voucher specimen from different museums. Genetic data from the Southern Levant populations were compared with sequences representing major clades of the group obtained from 25 , 26 , 28 , 34 .…”
Section: Methodsmentioning
confidence: 99%
“…It was described as a separate species under the name Elaphis sauromates (see: Strauch, 1873), followed by being synonymized with Coluber quatuorlineatus Bonnaterre, 1790, and subsequently treated as its subspecies C. quatuorlineatus sauromates (Boulenger, 1894). At the beginning of the 21st century, morphological and molecular-phylogenetic studies justified the species status of E. sauromates (Helfenberger, 2001; Lenk, Joger & Wink, 2001; Utiger et al, 2002) and this view has been largely accepted to date (Sindaco, Venchi & Grieco, 2013; Sillero et al, 2014; Wallach, Williams & Boundy, 2014; Jablonski, Soltys & Simonov, 2019). Aside from confirming the separate species status of E. sauromates , early genetic studies found a surprisingly high genetic distance between populations from Kazakhstan and eastern Turkey (5.0–6.5% in Lenk, Joger & Wink, 2001 or even 7.6% in Huang et al, 2012), which was quite similar to the distances between E. sauromates and E. quatuorlineata , E. dione and E. bimaculata Schmidt, 1925 , E. quadrivirgata (Boie, 1826) and E. carinata (Günther, 1864), or between E. quadrivirgata and E. schrenckii (Strauch, 1873) (Utiger et al, 2002; Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Five protein-coding genes (ND1, ND2, ND3, COXII, and COXIII) are inferred to terminate with an incomplete stop codon T--; five protein-coding genes (ATP8, ATP6, ND4L, ND5, and CYTB) share the typical termination codon TAA; COXI and ND6 have stop codon AGA, and ND4 use AGG as a stop codon. For 13 protein-coding genes, the A þ T content ranges from 52.58% to 61.73%, which is higher than that of G þ C (Jablonski et al 2019). In addition, we detected that 18 nucleotides from nine locations overlapped with the length of overlapped sequence of 1-5 bp, whereas there are totally 51 bp intergenic nucleotides in seven locations with the length of intergenic spacer of 1-33 bp.…”
Section: Colubridae; Mitochondrial Genome; Pseudoxenodon Macropsmentioning
confidence: 92%
“…For 13 protein-coding genes, the A + T content ranges from 52.58% to 61.73%, which is higher than that of G + C (Jablonski et al. 2019 ). In addition, we detected that 18 nucleotides from nine locations overlapped with the length of overlapped sequence of 1–5 bp, whereas there are totally 51 bp intergenic nucleotides in seven locations with the length of intergenic spacer of 1–33 bp.…”
mentioning
confidence: 99%